Evaluation Model of Private Pension Fund Activity on the Basis of the Theory of fractals Модели оценки деятельности НПФ на основе теории фракталoв - Prokopovich Svetlana V.; Tutova Svetlana A. (Problemi Ekonomiki, 2012)
The article is devoted to the problem of evaluation of the dynamics of indicators of non-state pension funds activities of Ukraine on the basis of the fractals theory application. Статья посвящена проблеме оценки динамики показателей деятельности негосударственных пенсионных фондов Украины на основе применения теории фракталов.